Machado de Assis and Carolina Maria de Jesus: from the trajectory to the writing of Brazilian social violence - Silva, Eliane da Conceição (Universidade Estadual Paulista / UNESP, 2018)
This paper aims to approach the trajectories and writing of two fundamental writers of Brazilian literature, Machado de Assis (1839-1908) and Carolina Maria de Jesus (1914-1977), and to analyze the way in which both dealt with and represented Brazilian social violence in their work. Thus, the analysis focuses especially on the story “Pai contra mãe”, by Machado de Assis, and in the book “Quarto de despejo: diário de uma favelada”, by Carolina Maria de Jesus. The purpose of the work is to investigate some aspects of the path of Machado de Assis and Carolina Maria de Jesus, taking as reference the insertion of both writers in the literary field, as well as the way they represented certain elements of Brazilian social violence.